Interleukin-2, interleukin-6 and T regulatory cells in peripheral blood of patients with Behcet's disease and recurrent aphthous ulcerations - NAMDAR PEKİNER, FİLİZ MEDİHA; BORAHAN, MEHMET OĞUZ (WILEY, 2012)
BACKGROUND: One of the factors involved in the pathogenesis of Behcet disease (BD) and recurrent aphthous ulcerations (RAU) is a cell-mediated immune response in which several cytokines (interleukin-2, interleukin-6) and T regulatory cell (T reg cell) population seem to play a major role. The aim of this study was to measured the interleukin-2 (IL-2), interleukin-6 (IL-6) levels and analysis of CD4(+) CD25(+) Foxp-3(+) Treg cells in peripheral blood from patients with BD and RAU. In addition; we also analysed peripheral blood from healthy subjects for comparison. METHODS: Thirty patients (15 men and 15 women) with BD, 30 patients (12 men and 18 women) with RAU and 15 healthy control subjects (nine men and six women) participated in the study. Analysis of CD4(+) CD25(+) Foxp-3(+) Treg cells, IL-2 and IL-6 levels have been measured in flow cytometry. RESULTS: No statistical differences were observed in the serum levels of IL-2 and IL-6 between BD and RAU patients, and healthy subjects. Although there were no statistical differences in the number of CD4(+) CD25(+) Foxp-3(+) cells between groups, there were statistically significant differences in the number of CD4(+) CD25(bright) Treg cells. CD4(+) CD25(bright) Treg cells were significantly increased in BD and RAU patients compared to healthy subjects. Statistical analysis revealed no difference according to the number of CD4(+) CD25(bright) cells between BD and RAU patients. CONCLUSIONS: These results indicate that CD4(+) CD25(bright) T regulatory cells may be contributing factor in the pathogenesis of BD and RAU. J Oral Pathol Med (2012) 41: 7379
Keywords: Behcet's disease; cytokine; IL-2; IL-6; recurrent aphthous ulcerations; T regulatory cell; NECROSIS-FACTOR-ALPHA; IMMUNOLOGICAL-TOLERANCE; TNF-ALPHA; EXPRESSION; CYTOKINES; IL-6; RECEPTOR; LESIONS; FOXP3; GAMMA